Carotid Disease - Jacobsen Cobra, Giovana; Burgos Garcia, Carolyn; Abreu, Phillipe; Mariúba, Jamil Victor de Oliveira [UNESP]; Sobreira, Marcone Lima [UNESP]; Malgor, Rafael (Springer Nature, 2025)
Cerebrovascular disease is an important cause of morbidity and mortality today. In the United States, there are an estimated 700,000 cases of stroke annually (85% ischemic) [1].